Teacher Perceptions and Practices of Tajwid and ‘Ilm al-Aṣwāt in Arabic Pronunciation Instruction: A Case Study at Madrasah Ibtidaiyah - Faturohman, Muhammad Miftah; Athallah, Muhammad Hanif; Marlina, Lina; Salim, Irfan (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
Effective Arabic pronunciation instruction at the primary education level relies heavily on how teachers conceptualize both traditional recitation rules (tajwid) and modern linguistic frameworks ('ilm al-aswat). Investigating teacher perceptions and practices is, therefore, critical to optimizing pedagogical approaches and ensuring a balanced integration of religious and communicative language skills. This study aims to analyze teachers' perceptions and practices regarding tajwid and 'ilm al-aswat in Arabic language learning at the Madrasah Ibtidaiyah level, as well as to examine the degree of alignment between them. The study employed a qualitative case study design, focusing on an Arabic teacher at MI Yayasan Putri Siti Hajar as the research subject. Data were collected through in-depth interviews and classroom observations and analyzed using data reduction, data display, and conclusion-drawing techniques. The findings reveal that the teacher has a strong perception of tajwid as the primary foundation for pronunciation, but lacks awareness of 'ilm al-aswat as a broader linguistic framework. In practice, phonological elements are implicitly present through tajwid-based approaches, such as pronunciation drills and imitation methods; however, the learning process remains intuitive and unsystematic. The dominance of the qawā‘id wa tarjamah method and reliance on textbooks further limit innovation and the development of communicative competence. These findings indicate partial alignment between perception and practice, yet also reveal a conceptual gap in which phonological practices are not supported by adequate scientific understanding. Therefore, integrating tajwid as a phonetic foundation with 'ilm al-aswat as a linguistic framework is essential to achieve more systematic, comprehensive, and communicative Arabic language learning.